NIR absorbing diferrocene-containing meso-cyano-BODIPY with a UV-Vis-NIR spectrum remarkably close to that of magnesium tetracyanotetraferrocenyltetraazaporphyrin. Issue 77 (6th September 2016) - Didukh, Natalia O.; Zatsikha, Yuriy V.; Rohde, Gregory T.; Blesener, Tanner S.; Yakubovskyi, Viktor P.; Kovtun, Yuriy P.; Nemykin, Victor N.
Abstract : Diferrocene-containing meso -cyano-BODIPY (4 ) was prepared and characterized by spectroscopy, X-ray crystallography, and DFT calculations. Abstract : Diferrocene-containing meso -cyano-BODIPY (4 ) was prepared by the direct cyanation/oxidation reaction of symmetric BODIPY1 followed by Knoevenagel condensation with ferrocenealdehyde. Ferrocene-containing BODIPY4 was characterized by a variety of spectroscopic, electrochemical, and theoretical methods and its UV-Vis-NIR spectrum has a striking similarity with a UV-Vis-NIR spectrum of the previously reported magnesium 2(3), 7(8), 12(13), 17(18)-tetracyano-3(2), 8(7), 13(12), 18(17)-tetraferrocenyl-5, 10, 15, 20-tetraazaporphyrin.